Immunohistochemical detection of estrogen receptor beta in alveolar bone cells of estradiol-treated female rats: possible direct action of estrogen on osteoclast life span - Cruzoe-Souza, Mady; Cerri, Estela Sasso [UNESP]; Cerri, Paulo Sérgio [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
The role of estrogen in bone resorption has been specifically related to the effect of estrogen on the signalling pathway that inhibits the formation of osteoclasts. However, osteoclast apoptosis and a significant reduction in the number of these cells have been observed in the alveolar bone of female rats treated with estradiol. In the present study, the expression of estrogen receptor beta (ER beta) in the cells of alveolar bone was evaluated in estradiol-treated and -untreated female rats. In order to test the possible direct action of estrogen on osteoclasts, the relationship between apoptosis and ER beta expression in these cells was also analysed. The animals received estradiol for 14 days and the alveolar bone fragments were embedded in paraffin for the quantification of tartrate-resistant acid phosphatase-positive osteoclasts. The expression of ER beta and apoptosis in the osteoclasts were evaluated by ER beta immunohistochemistry and Terminal deoxynucleotidyl transferase-mediated dUTP Nick-End Labelling (TUNEL) methods, respectively. To confirm osteoclast death by apoptosis, these cells were analysed under transmission electron microscopy. Some osteoclasts from estradiol-treated animals were found to be undergoing apoptosis and the number of tartrate-resistant acid phosphatase-positive osteoclasts was significantly reduced. ER beta immunolabelling was observed in the cytoplasm and nuclei of active osteoblasts, osteocytes and osteoclasts in both groups, suggesting a direct participation of estrogen on alveolar bone cells. However, following estradiol treatment, a strong ER beta immunolabelling was often observed in the TUNEL-positive osteoclasts. Therefore, these results indicate that, in addition to the other signalling pathway, the reduction of alveolar bone resorption is also related to a direct action of estrogen on osteoclasts, promoting apoptosis in these cells, via ER beta.
Keywords: alveolar bone; apoptosis; bone cells; estrogen receptor beta; osteoclast